2014
DOI: 10.1111/weng.12073
|View full text |Cite
|
Sign up to set email alerts
|

English in the Kingdom of Saudi Arabia

Abstract: This paper examines the history, politics and discourses around the (teaching of) English language in the Kingdom of Saudi Arabia (KSA). In addition to discussing the issues and debates around English language, this paper also looks at whether and how English has been localised to suit the local needs and practices. Based on an analysis of English language textbooks used in KSA, the paper shows that Saudi English mostly follows and ascribes to the grammatical norms of standard Englishes. The paper does identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
194
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(200 citation statements)
references
References 16 publications
5
194
1
Order By: Relevance
“…Tash ma Tash (comedy show) or Althaminah (talk show). However, the focus of this study is not to localise the textbooks as some earlier studies suggested in the literature of this study (Mahboob and Elyas 2014). Localising the current EFL textbooks is only part of the solution.…”
Section: The Dominance Of Western Culture Represented On Tv Programmesmentioning
confidence: 96%
See 3 more Smart Citations
“…Tash ma Tash (comedy show) or Althaminah (talk show). However, the focus of this study is not to localise the textbooks as some earlier studies suggested in the literature of this study (Mahboob and Elyas 2014). Localising the current EFL textbooks is only part of the solution.…”
Section: The Dominance Of Western Culture Represented On Tv Programmesmentioning
confidence: 96%
“…There exists therefore a need for a delicate balance between an acceptance of history and the prevention of further hegemony at the level of ELT. Mahboob and Elyas (2014) commented on the fact that English in the KSA is not a "neutral language". It is not value-neutral.…”
Section: Some Of Relevant Studies Found In Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…He further elaborates that people from different cultures have adopted the language to express themselves based on their cultures which leads to 'nativisation' of language and development of new varieties of English. Examples of these varieties of English include Pakistani English, Saudi English, Korean English, Singaporean English and Indian English [2][3][4][5][6]. For Muslims, they do not only use the language in communication, education, politics and business but also as a means to convey the message of Islam to the global audience, especially to non-Muslim English speaking audience.…”
Section: Introductionmentioning
confidence: 99%